The Relationship Between Macronutrient Intake And Menarche Age in Adolescent Girls At Junior High School 13 Padang - Sabrina, A`thifa; Hardisman, Hardisman; Yulizawati, Yulizawati; Rita, Rauza Sukma; Iffah, Ully; Fitria, henni (Universitas Andalas, 2025)
Menarche is the first menstrual period that indicates that a woman has reached biological maturity. The age of menarche continues to decline over time and is influenced by various factors such as nutrition, genetics, and socioeconomics. The intake of macronutrients such as carbohydrates, proteins, and fats plays a role in the maturation process of reproductive and hormonal organs that affect the age of menarche. Changes in nutrient consumption patterns among adolescents today can have an impact on the earlier or delayed age shift of menarche which can be a sign of developmental or hormonal problems. This study used an associative analytical design with a cross sectional approach and purposive sampling techniques for 55 respondents. The instrument used was the SQ-FFQ questionnaire to measure macronutrient intake with the results of measuring total energy and menarche age data obtained through interviews. The results of the study showed that 67.3% of respondents had no more energy intake, 32.7% had more energy intake, and 85.5% had normal menarche age, 14.5% abnormalized menarche age. The results of the analysis of Macronutrient energy intake with menarche age with the Yates Correction or Continuity Correction test were obtained p = 0.125. These results show that there is no relationship between macronutrient energy intake and menarche age in adolescent girls at SMPN 13 Padang.Based on the results of the study, it can be concluded that there is no statistically significant relationship between macronutrient energy intake and menarche age. It is hoped that the age of menarche is influenced by many factors apart from macronutrient intake, namely nutritional quality, hormones, and socio-economic factors.